2018
DOI: 10.1038/s41598-018-25610-6
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Huaiqihuang extractum protects against cisplatin-induced nephrotoxicity

Abstract: Cisplatin is a commonly used chemotherapeutic agent in the treatment of different types of malignant tumors, but nephrotoxicity limits its usage. Therefore, in this study, we aimed to determine the possible protective effect of Huaiqihuang (HQH) extractum, a kind of Chinese herbal complex that consists of Trametes robiniophila Murr., Lycium barbarum and Polygonatum sibiricum, against nephrotoxicity induced by cisplatin in mice. We found that pretreatment with HQH significantly attenuated the cisplatin-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 37 publications
4
29
0
Order By: Relevance
“…According to Liu et al, HQH was found to downregulate the expression of proapoptotic proteins Bax, Cyt C, and caspase 3 and upregulate the expression of antiapoptotic proteins Bcl-2 [9]. Similarly, Fang et al found that, compared with the control group, the proportion of proapoptotic and antiapoptotic proteins in the HP-1 treatment group has a relatively balanced ratio and the apoptosis was reduced accordingly [8,37]. Furthermore, GRP78 can bind and inhibit the activity of proapoptotic protein BIK on endoplasmic reticulum [38], promoting the expression of bcl-2 so as to inhibit cell apoptosis [39,40].…”
Section: 32mentioning
confidence: 99%
See 4 more Smart Citations
“…According to Liu et al, HQH was found to downregulate the expression of proapoptotic proteins Bax, Cyt C, and caspase 3 and upregulate the expression of antiapoptotic proteins Bcl-2 [9]. Similarly, Fang et al found that, compared with the control group, the proportion of proapoptotic and antiapoptotic proteins in the HP-1 treatment group has a relatively balanced ratio and the apoptosis was reduced accordingly [8,37]. Furthermore, GRP78 can bind and inhibit the activity of proapoptotic protein BIK on endoplasmic reticulum [38], promoting the expression of bcl-2 so as to inhibit cell apoptosis [39,40].…”
Section: 32mentioning
confidence: 99%
“…Liu et al demonstrated that Huaier inhibits the expression of TNF-α, p-NF-κB p65, and IκB, thereby inhibiting the apoptotic NF-κB signaling pathway and protecting the kidney [9]. Guo et al found that in CP-induced nephropathy, Huaier can reduce the TLR4/NF-κB pathway to protect the kidneys [37]. Adding Huaier to CP-induced nephropathy, it was found that it can downregulate the PI3K/Akt/m-TOR/NF-κB signaling pathway in cisplatin nephrotoxicity cells and downregulate the expression of p-NF-κB.…”
Section: 32mentioning
confidence: 99%
See 3 more Smart Citations